HUBUNGAN RASIO LINGKAR PINGGANG PINGGUL DAN INDEKS MASSA TUBUH TERHADAP TEKANAN DARAH PADA MIDDLE AGE (45-59 TAHUN) DI WILAYAH KERJA PUSKESMAS KARANGMALANG KOTA SEMARANG - Estia Mukiwanti; Muwakhidah Muwakhidah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Hypertension is a non-communicable disease with the highest incidence compared to a combination of all other causes of death. Hypertension accounts for 6% of deaths worldwide. The prevalence of hypertension in Semarang was 49.1%, the greatest incidence in women and age group 45-65 years.Obesity indicators associated with hypertension include Body Mass Index and Hip Waist Ratio. The purpose of this research is to know the relation of Waist Circumference Ratio and Body Mass Index to blood pressure at middle age (45-59 years) in Polaman village of Semarang City. The research method used observational research with cross sectional approach. The subject of this research is the population of Polaman villagers aged 45-59 years. Sampling was done by total population and got 31 samples. Subjects who met the inclusion and exclusion criteria (direct interview results) measured blood pressure, waist circumference, hip circumference, weight and height. The data were tested statistically with Rank Spearman correlation. The result of research is as much as 90,9% have the ratioof Hip Waist Circumference high in woman and 77,8% have high hips Waist Ratio in man. Total Hip Waistage Ratios total high of 87.1%. As many as 74.2% have fatty Body Mass Index. Normal female systolic blood pressure was 63.6 and men were 55.6% while diastolic blood pressure for women and men was 59.1 and 55.6%, respectively. The result of bivariate variable of waist circle ratio with systolic blood pressure showed p value = 0,032; R = 0,386 whereas variable of Waist Hip Ratio with diastolic blood pressure value p = 0,003; R = 0,521. Variable Body Mass Index with systolic blood pressure p value = 0.583 and Body Mass Index with diastolic blood pressure p value = 0.703. The conclusion of research is that there is a relationship between Waist Circumference Ratio to systolic and diastolic blood pressure. There is no association between the Body Mass Index against systolic and diastolic blood pressure. Keywords: hypertension, waist hip ratio, BMI, blood pressure